Pendidikan Keluarga Berencana (KB) Dalam Keluarga Islam: Kajian Living Hadis Dalam Menguatkan Keluarga Sejahtera - Syamsu Rijal (Jurnal Serambi Ilmu, 2024)
In this paper, talking about family planning according to the perspective of living hadith, in relation to government programs in implementing the program with the aim of preventing the explosion of the birth rate in Indonesia, another mission of this program is aimed at welfare and saving many mothers and babies. In this study, the writing style of the living hadith is more used, namely putting forward and quoting the hadiths related to themes. The hadith raised in the theme of family planning is a hadith in which a man came to Rasulullah SAW, and said he often slept with his female slave and did not want her to become pregnant, then Rasulullah advised her by doing ’azl. This theme explains the various viewpoints of family planning in terms of Islamic law, views of human rights, and also disagree with family planning.